2011
DOI: 10.1038/icb.2011.71
|View full text |Cite
|
Sign up to set email alerts
|

ISCOMATRIX vaccines mediate CD8+ T‐cell cross‐priming by a MyD88‐dependent signaling pathway

Abstract: Generating a cytotoxic CD8+ T-cell response that can eradicate malignant cells is the primary objective of cancer vaccine strategies. In this study we have characterized the innate and adaptive immune response to the ISCOMATRIX adjuvant, and the ability of vaccine antigens formulated with this adjuvant to promote antitumor immunity. ISCOMATRIX adjuvant led to a rapid innate immune cell response at the injection site, followed by the activation of natural killer and dendritic cells (DC) in regional draining lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 61 publications
6
101
1
Order By: Relevance
“…In our study, the induction of a number of cytokines (e.g., IL-6, CCL2, and CCL3) may have been dependent on MPL (8), whereas the induction of IL-1b may have been due to QS-21 because IL-1b induction is associated with the activation of the inflammasome, and the activation of the inflammasome has been observed with QuilA (54). In addition, QS-21 is likely to have played a role in CD8 + T cell induction in the mouse model used in this study, perhaps mediated by a particular population of DCs, as reported recently (35). The contributory roles of MPL and QS-21 in the response are currently under investigation.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In our study, the induction of a number of cytokines (e.g., IL-6, CCL2, and CCL3) may have been dependent on MPL (8), whereas the induction of IL-1b may have been due to QS-21 because IL-1b induction is associated with the activation of the inflammasome, and the activation of the inflammasome has been observed with QuilA (54). In addition, QS-21 is likely to have played a role in CD8 + T cell induction in the mouse model used in this study, perhaps mediated by a particular population of DCs, as reported recently (35). The contributory roles of MPL and QS-21 in the response are currently under investigation.…”
Section: Discussionmentioning
confidence: 47%
“…CD11c + cell depletion was achieved by injecting DT into animals that had bone marrow transplants from mice transgenic for DTR driven by the CD11c promoter (35). Transgene expression rendered the cells sensitive to the lethal effect of DT.…”
Section: Improved T Cell Response By As01 Is Mediated By Mhcii High Dcsmentioning
confidence: 99%
“…Recent studies have demonstrated the ability of IMX to enhance MHC class I cross-presentation and produce long-lasting Ab and T cell immune responses (20)(21)(22)(23)(24). The dependence on the adapter protein MyD88 for cellular immunity to an IMX vaccine remains unresolved (24). Similarly, MyD88 has been implicated in the mechanism of MF59 adjuvanticity in mice (25,26).…”
mentioning
confidence: 99%
“…Ags can be formulated with IMX to produce IMX vaccines (18,19). Recent studies have demonstrated the ability of IMX to enhance MHC class I cross-presentation and produce long-lasting Ab and T cell immune responses (20)(21)(22)(23)(24). The dependence on the adapter protein MyD88 for cellular immunity to an IMX vaccine remains unresolved (24).…”
mentioning
confidence: 99%
“…Subjects who received three intramuscular doses of this vaccine at 3-week intervals experienced a 50% decrease in viral shedding and a 69% reduction in the rate of genital lesions compared to placebo, which continued for 6 months postvaccination (55). T cell responses have not been reported for this trial, but adjuvants with compositions similar to that of matrix-M2 have been shown in animal models to promote major histocompatibility complex (MHC) class I cross-presentation and the promotion of CTL responses (58). It will be interesting to learn if CD8 T cell responses specific for ICP4 are detectable in these vaccinated individuals.…”
Section: Figmentioning
confidence: 99%